SALES LEVEL FORECASTING OF JASMINE FLOWERS WITH EXPONENTIAL SMOOTHING METHOD - Harvei Desmon Hutahaean; Muhammad Dominique Mendoza; Charles Fransiscus Ambarita (Sean Institute, 2022)
The forecasting process is used to support the decisions of a company to get maximum profit. The sales of jasmine flowers have been growing rapidly lately, especially for the needs of environmental friendly decorative plants sector. It is necessary to predict the sales value of these flowers to prevent loss in business income during Covid-19 pandemic. The Exponential Smoothing method has been widely used for forecasting because it has a fairly good performance. The Exponential Smoothing method has several alpha parameters that are used, namely 0.1; 0.5; 0.9 to support calculations that will be used in forecasting. With these methods, calculations can be carried out to find the best optimal value with the smallest error rate. The chosen forecasting method is used to forecast jasmine flowers sales. Based on the results of the MAD (Mean Absolute Deviation) calculation, it can be seen that the smallest MAD value can be obtained at a value of Î± = 0.1, is 61.17. Forecasting the sale of jasmine flowers using the Exponential Smoothing method is most suitable for UD. Susan Melati with a value of Î± = 0.1. This shows that the historical pattern of actual data does not fluctuate or is relatively stable over time.